Clinical Evaluation of Predisposing Factors of Hypoglycaemia in Diabetic Patients (TAJ: Journal of Teachers Association, 2023)
Background: Hypoglycemia is a common medical problem in diabetic patients, and the potential range of morbidity and mortality in diabetic patients exposed to hypoglycemia is significant. The study was conducted to evaluate the predisposing factors of hypoglycemia in diabetic populations.Methods: This is a descriptive cross-sectional study carried out in the indoor and outdoor patient department of BIRDEM hospital, Dhaka, Bangladesh, from July 2009 to December 2009 after ethical approval in conformity with the revised 1964 Helsinki declaration. Following informed written consent, a total of 50 diabetic patients having hypoglycemia were finally included. Data analysis was done using SPSS 17.Results: In the study population, significant members of hypoglycemic episodes were found in middle age (31-70) insulin-treated patients and poor diabetic education and in those who had other concomitant diseases. Poor dietary compliance (Reduced meal intake in 50% of cases and missed meal in 34% of cases) and lack of proper diabetic education about early recognition and treatment of hypoglycemia also appeared as important contributory factors. Noncompliance with regular exercise (40%) and unaccustomed exercise (4%) contribute to hypoglycemia. A significant number of hypoglycemic patients have chronic renal insufficiency (68%).Conclusion: Hypoglycemia is common in the diabetic population who have poor knowledge and practice about diet, drug exercise technique of, use of insulin devices, and have an underlying systemic illness. So more rational education system and appropriate management of systemic diseases regarding the prevention and treatment of hypoglycemia is demanded by our diabetic patients.TAJ 2022; 35: No-2: 143-149